#### Answer

$f^{-1}(x) = \frac{2x}{x - 3}$

#### Work Step by Step

$f(x) = \frac{3x}{x - 2}$
$y = \frac{3x}{x - 2}$
y(x - 2) = 3x
yx - 2y = 3x
yx - 3x = 2y
x(y - 3) = 2y
$x = \frac{2y}{y - 3}$
$f^{-1}(x) = \frac{2x}{x - 3}$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(x) = \frac{2x}{x - 3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.